Comparative study of Trigonella foenum-graecum L. varieties in the Middle East by using protein pattern and seed morphology - El-Shabasy, Ahmed (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2024)
This study illustrates the situation of the relation between different varieties of Trigonella foenum-graecum L. not in the same one country but in different countries in the Middle East area; Algeria, Egypt, Ethiopia, India, Iran, Sudan, Tunisia, Turkey and Yemen. This comparative study explained the origin of the studied plant species and the evolutionary trends by using protein pattern and seed morphology showing the ancestral origin arisen upper Middle East region. This study explored the global changes and impacts on variety distribution.